Boosting Students' Mathematical Problem-Solving Skills with PBL-Based LiveWorksheets: Focus on Whole Numbers and Fractions Topic - Usqo, Urwatil; Hutapea, Nahor Murani; Kartini, Kartini (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2024)
Problem solving skills is one of the important skills that students must master through learning mathematics. One alternative to improve students' mathematical problem-solving skills is using the Problem-based Learning (PBL) learning model combined with technology-based learning media. This research aims to produce PBL-based electronic student worksheets (e-worksheets) on the topic of whole numbers and fractions that are valid, practical and effective to improve students' mathematical problem-solving skills. The development of e-worksheets uses a 4D development model involving seventh-grade students from one of the junior high schools in Rokan Hulu, Riau, Indonesia as field test subjects. The results of data analysis show that the e-worksheet developed using LiveWorksheet application has met the valid criteria based on experts judgement and practical based on the practicality questionnaires. E-worksheets have also been proven effective in improving students' mathematical problem-solving skills with an average N-gain at high criteria.